A multivariate analysis of reported quality of life among medical students in Jordan using the WHOQOL-BREF - Mohammad Hamad; Saba Al Smadi; Diana Arabiat (Journal of Education and Health Promotion)
BACKGROUND: Low quality of life (QoL) in university students is often associated with unhealthy lifestyle and negative impacts on students’ ability to learn and succeed. To date, no research has examined the QoL of medical students in Jordan or the demographic factors that may associate with lower QoL. MATERIALS AND METHODS: A quantitative, cross-sectional study with a descriptive design was chosen for this study. Participants were 512 medical students from one public university in Jordan. The Arabic version of the World Health Quality of life-brief survey (WHOQOL-BREF) was used to collect data online from students. RESULTS: Regarding the overall QoL, most students rated their QoL (67%) and health satisfaction (64%) as good. There were significant differences across the various QoL domains in relation to gender, academic achievements, and academic year level (P < 0.005). The physical health domain had the highest mean score (60.60 ± 17.00), while psychological health domain had the lowest mean score (56.90 ± 17.75). CONCLUSION: Lower QoL scores among female students may reflect a socially disadvantaged environment and poorer well-being for female medical students. Lower scores in physical and psychological domains among students with lower GPAs suggest the need for initiating well-being programs to promote a study-friendly atmosphere.